GUIDANCE IN PREPARATION OF BUSINESS PLANS AND FINANCIAL REPORTS IN VILLAGE-OWNED ENTERPRISES - Darmawati Muchtar; Jullimursyida; Naufal Bachri; Teuku Zulkarnaen; Mutia Rahmah; Mentari Riswanti; Defiah Anggarini Br Manurung (RADJA PUBLIKA, 2025)
This community service program was conducted in Gampong Reuleut Timu, Muara Satu District, North Aceh Regency. The main issue faced by the partner village was the suboptimal management of BUMDes assets, particularly in the preparation of business plans and financial reports that are transparent and accountable. Village officials, including the Geuchik, treasurer, and community members, lack adequate understanding of proper governance mechanisms. The aim of this program was to provide training and assistance to village officials in preparing business plans and financial statements for BUMDes in accordance with good governance principles. The methods employed included workshops and technical mentoring, involving 20 village officials as participants. Evaluation was carried out through post-activity monitoring. The results showed a significant improvement in participants' understanding, with 85% being able to independently prepare both business plans and financial reports.